Diagnostic accuracy of transthoracic echocardiography for acute type A aortic syndrome: A systematic review and meta-analysis - Hsin-Tzu Yeh; Sz-Wei Lu; Tzu-Heng Cheng; Jian-Xun Lu; Chien-Han Hsiao; Chieh-Ching Yen (Biomedical Journal)
Background: Transthoracic echocardiography (TTE) is currently recognized as the potential first-line imaging test for patients with suspected acute type A aortic syndrome (AAAS). Direct TTE sign for detecting AAAS is positive if there is an intimal flap separating two aortic lumens or aortic wall thickening seen in the ascending aorta. Indirect TTE sign indicates high-risk features of AAAS, such as aortic root dilatation, pericardial effusion, and aortic regurgitation. Our aim is to summarize the existing clinical evidence regarding the diagnostic accuracy of TTE and to evaluate its potential role in the management of patients with suspected AAAS. Methods: We included prospective or retrospective diagnostic cohort studies, written in any language, that specifically focused on using TTE to diagnose AAAS from databases such as PubMed, EMBASE, MEDLINE, and the Cochrane Library. The pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR) , and hierarchical summary receiver-operating characteristic (HSROC) curve were calculated for TTE in diagnosing AAAS. We applied Quality Assessment of Diagnostic Accuracy (QUADAS-2) tool and Grading of Recommendations, Assessment, Development and Evaluation (GRADE) quality assessment criteria. Results: Ten studies (2886 patients) were included in the meta-analysis. The pooled sensitivity and specificity of direct TTE signs were 58% (95% CI, 38–76%) and 94% (95% CI, 89–97%). For any TTE signs, the pooled sensitivity and specificity were 91% (95% CI, 85–94%) and 74% (95% CI, 61–84%). The diagnostic accuracy of direct TTE signs was significantly higher than that of any TTE signs, as measured by the area under the HSROC curve [0.95 (95% CI, 0.92–0.96) vs. 0.87 (95% CI, 0.84–0.90)] in four studies. Conclusions: Our study suggests that TTE could serve as the initial imaging test for patients with suspected AAAS. Given its high specificity, the presence of direct TTE signs may indicate AAAS, whereas the absence of any TTE signs, combined with low clinical suspicion, could suggest a lower likelihood of AAAS.